A Longitudinal Study of T2 Mapping Combined With Diffusion Tensor Imaging to Quantitatively Evaluate Tissue Repair of Rat Skeletal Muscle After Frostbite - Gao, Yue; Lu, Zhao; Lyu, Xiaohong; Liu, Qiang; Pan, Shinong (Frontiers in Physiology, 2021)
Purpose:T2 mapping and diffusion tensor imaging (DTI) enable the detection of changes in the skeletal muscle microenvironment. We assessed T2 relaxation times, DTI metrics; performed histological characterization of frostbite-induced skeletal muscle injury and repair; and provided diagnostic imaging biomarkers. Design and Methods: Thirty-six Sprague Dawley rats (200±10 g) were obtained. Thirty rats were used for establishing a skeletal muscle frostbite model, and six were untreated controls. Functional MR sequences were performed on rats on days 0, 3, 5, 10, and 14 (n = 6 per time point). Rats were then sacrificed to obtain the quadriceps muscles. Tensor eigenvalues (λ1, λ2, λ3), mean diffusivity (MD), fractional anisotropy (FA), and T2 values were compared between the frostbite model and control rats. ImageJ was used to measure the extracellular area fraction (EAF), muscle fiber cross-sectional area (fCSA), and skeletal muscle TNF-α and Myod1 expression. The correlation between the histological and imaging parameters of the frostbitten skeletal muscle was evaluated.Kolmogorov–Smirnoff test, Leven’s test, one-way ANOVA, and Pearson coefficient were used for analysis. Results: T2 relaxation time of frostbitten skeletal muscle was higher at all time points (p<0.001). T2 relaxation time correlated with EAF, and TNF-α and Myod1 expression (r=0.47, p=0.004; r=0.91, p<0.001; r=0.85, p<0.001). The average tensor metrics (MD, λ1, λ2, λ3) of skeletal muscle at 3 and 5 d of frostbite increased (p <0.05), and fCSA correlated with λ1, λ2, λ3, and MD (r = 0.72, p = 0.93 × 10-6, r = 0.61, p = 0.93 × 10-4, r = 0.59, p = 0.21 × 10-3, r = 0.34, p = 0.047). Conclusion: T2 mapping and DTI imaging detect frostbite-induced skeletal muscle injury early. This combined approach can quantitatively assess skeletal muscle repair and regeneration within two weeks of frostbite. Imaging biomarkers for the diagnosis of frostbite were suggested.